2019
DOI: 10.1177/0013124519842654
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Parental Involvement and Achievement in East Asian Countries

Abstract: Countless meta-analytic studies document the relation between parental involvement and achievement, but they mostly include studies conducted in the United States where parental involvement is framed as a policy issue. This is the first meta-analytic study focusing on East Asian countries characterized by high achievement levels, a comparatively standardized education system, and no policy encouraging family–school relations. A meta-analysis of 15 studies retrieved from an exhaustive search of the literature r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 67 publications
0
39
1
4
Order By: Relevance
“…Up to date, meta-analyses of SES and achievement all exclude attainment from their outcome measure (Harwell et al, 2017;Sirin, 2005;White, 1982). Among the multiple studies that examined parental involvement and academic outcomes (see Wilder, 2014;Kim, 2019), the only study that aggregated attainment measures with achievement measures is Fan and Chen (2001). A moderator analysis revealed no differences in ESs between achievement (school GPA, tests) and attainment categories ("other" category including postsecondary attainment, grade retention, teachers' rating, etc.)…”
Section: Overall Relation Between Ses and Achievement/attainmentmentioning
confidence: 99%
“…Up to date, meta-analyses of SES and achievement all exclude attainment from their outcome measure (Harwell et al, 2017;Sirin, 2005;White, 1982). Among the multiple studies that examined parental involvement and academic outcomes (see Wilder, 2014;Kim, 2019), the only study that aggregated attainment measures with achievement measures is Fan and Chen (2001). A moderator analysis revealed no differences in ESs between achievement (school GPA, tests) and attainment categories ("other" category including postsecondary attainment, grade retention, teachers' rating, etc.)…”
Section: Overall Relation Between Ses and Achievement/attainmentmentioning
confidence: 99%
“…For example, it was found that family SES emerged as the most relevant predictor of academic achievement in Language and Mathematics in Chile (Gubbins & Otero, 2019). There was a significant positive relationship between parental involvement and achievement in East Asian countries (Kim, 2020). Taken together, it may be asserted that school-level improvement efforts can be successful with the involvement and support of parents.…”
Section: Discussionmentioning
confidence: 99%
“…B. Barger et al, 2019;Hill & Tyson, 2009;Jeynes, 2005;Kim, 2020;Kim & Hill, 2015;Rosenzweig, 2001), ist die Gestaltung einer lernförderlichen Umgebung zuhause positiv mit der Schulleistung korreliert (z. B.…”
Section: Zusammenhänge Der Dimension Home-based Parental Involvementunclassified